Structural controls of auriferous quartz veins in the Karibib Area, southern central zone of the Pan-African Damara Belt, Namibia - Kitt, Shawn (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Earth Sciences))--Stellenbosch University, 2008.